Opportunities, challenges, and future perspectives of oncolytic virus therapy for malignant melanoma - Wang, Jia-Wen; Feng, Qi; Liu, Jia-Hui; Xun, Jian-Jun (Frontiers in Immunology, 2025)
Malignant melanoma is characterized by high heterogeneity, aggressive metastatic potential, and a profoundly immunosuppressive “cold” tumor microenvironment, contributing to broad therapeutic resistance and suboptimal responses to immunotherapy. Conventional PD-1 inhibitors yield an ORR of only 38%. As an emerging class of immunotherapeutic agents, oncolytic viruses (OV) induce ICD, promoting the release of DAMPs and activating innate immune pathways such as cGAS-STING, thereby transforming “cold” tumors into “hot” phenotypes and eliciting robust anti-tumor responses. Mechanistically, OV therapy increases the proportion of CD103+ dendritic cells (DCs) in lymph nodes from 5% to 25% and enhances DC–tumor synapse formation by 300%, facilitating efficient cross-presentation of tumor antigens and T-cell priming. Clinically, T-VEC combined with pembrolizumab achieves a 48.6% ORR with grade ≥3 AEs occurring in <20% of patients—superior to either monotherapy or conventional chemoradiotherapy. Nonetheless, OV therapy faces challenges including tumor heterogeneity, core mechanistic limitations, viral shedding risks, and regulatory hurdles. Over the next 5–10 years, single-cell RNA sequencing is expected to unravel molecular heterogeneity in melanoma, while CRISPR/Cas systems may enable the design of tailored OV to overcome resistance. Additional strategies such as serotype switching, JAK/STAT inhibition, and arming OV with hyaluronidase or STING agonists are under investigation to overcome immune and stromal barriers. Integration of artificial intelligence with biomarkers—such as neutralizing antibody titers, ISG expression, and STING methylation—may further enable personalized OV-based therapies. This review discusses OV therapy’s mechanisms, clinical impact, and future prospects in melanoma treatment.